2001
DOI: 10.1152/ajpheart.2001.281.3.h1274
|View full text |Cite
|
Sign up to set email alerts
|

Central volume expansion is pivotal for sustained decrease in heart rate during seated to supine posture change

Abstract: During prolonged, static carotid baroreceptor stimulation by neck suction (NS) in seated humans, heart rate (HR) decreases acutely and thereafter gradually increases. This increase has been explained by carotid baroreceptor adaptation and/or buffering by aortic reflexes. During a posture change from seated to supine (Sup) with similar carotid stimulation, however, the decrease in HR is sustained. To investigate whether this discrepancy is caused by changes in central blood volume, we compared (n = 10 subjects)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
16
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 27 publications
3
16
0
Order By: Relevance
“…The subjects were seated in an adjustable chair, whereby the upper body was manually tilted from upright vertical to horizontal supine and back to vertical again by moving the back support of the chair. During the test the legs were kept horizontal (22)(23)(24)(25). Each posture lasted 15 min.…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…The subjects were seated in an adjustable chair, whereby the upper body was manually tilted from upright vertical to horizontal supine and back to vertical again by moving the back support of the chair. During the test the legs were kept horizontal (22)(23)(24)(25). Each posture lasted 15 min.…”
Section: Methodsmentioning
confidence: 99%
“…In previous studies, we have shown that during a moderate anti-orthostatic tilt maneuver, which on an average better reflect the usual ambulatory human body posture changes than passive whole body tilting, HR decreases simultaneously with increases in SV and APP (21)(22)(23)(24)(25). Increases of the latter can be considered to reflect the pulsatile stimuli to the arterial baroreflexes for adjusting HR (21-24, 27).…”
Section: Mechanisms Of Bh Effects On Cardiovascular Variables During mentioning
confidence: 99%
See 3 more Smart Citations